2012
DOI: 10.5653/cerm.2012.39.4.161
|View full text |Cite
|
Sign up to set email alerts
|

Hysterosalpingo-contrast sonography: is possible to quantify the therapeutic effect of a diagnostic test?

Abstract: ObjectiveTo evaluate the effect of hysterosalpingo-contrast sonography (HyCoSy) on natural conception in the infertile patient.MethodsWe conducted a prospective observational study recruiting 180 patients admitted to Infertility Center of Ferrara University from January 2010 to February 2012. The essential inclusion criteria was the couple's desire to perform only diagnostic evaluation on infertility causes and to wait for natural conception before proceeding with further management. Couples were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 14 publications
8
23
2
1
Order By: Relevance
“…Hysterosalpingocontrast sonography (carried out like hydrotubation but with contrast medium) has a higher conception rate (22%). 8 The pregnancy rate was higher in the first month compared to other months which is in accordance to this study. 8 The increased infection rate was not there in this study neither in international studies and database review.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Hysterosalpingocontrast sonography (carried out like hydrotubation but with contrast medium) has a higher conception rate (22%). 8 The pregnancy rate was higher in the first month compared to other months which is in accordance to this study. 8 The increased infection rate was not there in this study neither in international studies and database review.…”
Section: Discussionsupporting
confidence: 91%
“…The success rate is lower in studies where lesser amount of fluid is used for hydrotubation. 8 The hydrostatic effect of the amount of fluid used can remove the obstructive elements in the tube and washing of tube with normal saline can dilute toxic and inflammatory factors. In this study, 50cc fluid was used daily to wash the tubes for 3days .There was a slight increase in discomfort of the patient in terms of lower abdominal pain, nausea and vomiting and right shoulder tip pain but greater chance of achieving the pregnancy makes even these complications agreeable to the womens compared to unsuccessful treatment with lesser fluid volume injected and lesser pain experienced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our infertility centre we noticed that spontaneous pregnancies often occurred in patients who underwent HyCoSy in the previous 3–6 months [24]. Lindborg et al [25], recently suggested a valid explanation for this phenomenon: the passage of the fluid through a partially occluded tube (minor adhesions, mucus plugs) could remove minor adhesions or buildup material caused by inflammatory processes and hence restore tubal patency.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly improved conception rate has been achieved by saline sonosalpingography in unexplained infertility [5][6][7] . Tubal flushing has previously proved to be one way of increasing the chance of acheiving pregnancy for couples with increased infertility and early stage of endometriosis 8 . Hydrotubation treatment can be administered in an outpatient clinic and represents a less invasive treatment alternative 9 .…”
Section: Introductionmentioning
confidence: 99%